Research methods in child language : a practical guide - Hoff, Erika, 1951- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
This is a comprehensive and accessible guide to the methods researchers use to study child language, written by experienced scholars in the study of language development. Presents a comprehensive survey of laboratory and naturalistic techniques used in the study of different domains of language, age ranges, and populations, and explains the questions addressed by each techniquePresents new research methods, such as the use of functional Near Infrared Spectroscopy (fNIRS) to study the activity of the brainExpands on more traditional research methods such as collection, transcription, and coding.
Research Methods in Child Language: A Practical Guide; Contents; List of Figures; List of Plates; Notes on Contributors; Acknowledgments; Preface; Part I Studying Infants and Others Using Nonverbal Methods; 1 Habituation Procedures; 2 Intermodal Preferential Looking; 3 The Looking-While-Listening Procedure; 4 Neuroimaging Methods; 5 Methods for Studying Language in Infants: Back to the Future; Part II Assessing Language Knowledge and Processes in Children Who Talk; 6 Assessing Phonological Knowledge; 7 Assessing Vocabulary Skills.
Includes bibliographical references and index.
Keywords: Children -- Language; Language awareness in children; Language acquisition -- Age factors; Language acquisition -- Research -- Methodology; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Psycholinguistics; Children -- Language; Language acquisition -- Age factors; Language acquisition -- Research -- Methodology; Language awareness in children; Taalontwikkeling; Kindertaal; Onderzoeksmethoden; Electronic books